Kaarina Maununtyttären sarkofagi Turun tuomiokirkossa - Ståhlberg, K. E.
mustavalkoinen
Keywords: kirkkorakennukset; haudat; sarkofagit; ikkunat; lasimaalaus; Suomi, Turku, Turun tuomiokirkko, Turku, Turun tuomiokirkko